2022
DOI: 10.3389/fgene.2022.908104
|View full text |Cite
|
Sign up to set email alerts
|

Immune Landscape and Classification in Lung Adenocarcinoma Based on a Novel Cell Cycle Checkpoints Related Signature for Predicting Prognosis and Therapeutic Response

Abstract: Lung adenocarcinoma (LUAD) is one of the most common malignancies with the highest mortality globally, and it has a poor prognosis. Cell cycle checkpoints play a central role in the entire system of monitoring cell cycle processes, by regulating the signalling pathway of the cell cycle. Cell cycle checkpoints related genes (CCCRGs) have potential utility in predicting survival, and response to immunotherapies and chemotherapies. To examine this, based on CCCRGs, we identified two lung adenocarcinoma subtypes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The findings revealed that RS strongly predicts outcomes in LUAD patients with various clinical characteristics, particularly in early LUAD patients ( Figures 7A–F ). In order to demonstrate the predictive performance of our model, we compared it with other models based on the TCGA-LUAD database, such as the published gene prediction models of Duan et al (2021) , Zhang et al (2022) , Yang et al (2022) , Xu and Chen, (2021) , Gong et al (2022) . Our model has the greatest c-index of nomogram compared to previously published lung cancer models, as indicated by the findings.…”
Section: Resultsmentioning
confidence: 99%
“…The findings revealed that RS strongly predicts outcomes in LUAD patients with various clinical characteristics, particularly in early LUAD patients ( Figures 7A–F ). In order to demonstrate the predictive performance of our model, we compared it with other models based on the TCGA-LUAD database, such as the published gene prediction models of Duan et al (2021) , Zhang et al (2022) , Yang et al (2022) , Xu and Chen, (2021) , Gong et al (2022) . Our model has the greatest c-index of nomogram compared to previously published lung cancer models, as indicated by the findings.…”
Section: Resultsmentioning
confidence: 99%
“…It is particularly important to identify new biomarkers of prognosis and develop more accurate prognostic models to predict the survival of patients with lung cancer to guide the treatment strategy. Previously reported prognostic models for ferroptosis-related genes, cell-cyclecheckpoints-related genes and aging-related-genes have exhibited promising results in predicting the prognosis in LUAD [14][15][16] . However, these biomarkers still have some limitations in terms of predictive power, and more accurate prognostic models are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Lung adenocarcinoma (LUAD) is a common form of lung cancer which also gets detected in the middle/late stages and therefore is hard to treat [45]. Yang et al (2022) used a dataset of gene expression profiles from 515 tumor samples and 59 normal tissues and split the dataset into two significantly different clusters; they further showed that using age, gender, pathological stages, and risk score as predictors of LUAD increased the prediction accuracy measures [46]. Liu, Lei, Zhang, and Wang (2022) used cluster analysis on enrichment scores of 12 stemness signatures to identify three LUAD subtypes, St-H, St-M and St-L for six different datasets [47].…”
Section: Methodsmentioning
confidence: 99%